The effect of autism risk level based on m-chat on children's emotional responses measured by cars at the pembina state special needs school in Medan - Annisa Amalia; Rahmahtrisilvia Rahmahtrisilvia (Lembaga Riset Mutiara Akbar, 2026)
This study aims to identify the level of autism risk in children using the Modified Checklist for Autism in Toddlers (M-CHAT), measure emotional responses using the Childhood Autism Rating Scale (CARS), and analyze the relationship between these variables. The research employed a descriptive quantitative approach with a case study design conducted at SLB-E Negeri Pembina Medan on March 9, 2026. The sample consisted of two children diagnosed with autism, selected purposively based on specific criteria and parental consent. Data were collected through observation, interviews with teachers, and M-CHAT questionnaires completed by parents, then analyzed descriptively by comparing M-CHAT and CARS scores. The findings indicate that children with moderate autism risk exhibit moderate emotional disturbances, while those with high autism risk show severe emotional disturbances. These results reveal a consistent trend that higher autism risk levels are associated with increased severity of emotional response disorders. This study highlights the importance of early autism risk detection as a foundation for developing targeted interventions, particularly in enhancing emotional abilities. The findings are expected to serve as a reference for educators, parents, and healthcare professionals in designing appropriate support strategies for children with autism